2019
DOI: 10.3390/cancers11121961
|View full text |Cite
|
Sign up to set email alerts
|

NF-kappa B Signaling-Related Signatures Are Connected with the Mesenchymal Phenotype of Circulating Tumor Cells in Non-Metastatic Breast Cancer

Abstract: The role of circulating tumor cells (CTCs), tumor microenvironment (TME), and the immune system in the formation of metastasis is evident, yet the details of their interactions remain unknown. This study aimed at exploring the immunotranscriptome of primary tumors associated with the status of CTCs in breast cancer (BCa) patients. The expression of 730 immune-related genes in formalin-fixed paraffin-embedded samples was analyzed using the multigenomic NanoString technology and correlated with the presence and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 60 publications
(67 reference statements)
0
24
0
Order By: Relevance
“…For each analyzed sample, correction and normalization were performed using nSolver 4.0 software, as previously described [ 14 ]. In brief, the background level was estimated by thresholding over the mean plus 2 standard deviations of the negative control counts.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For each analyzed sample, correction and normalization were performed using nSolver 4.0 software, as previously described [ 14 ]. In brief, the background level was estimated by thresholding over the mean plus 2 standard deviations of the negative control counts.…”
Section: Methodsmentioning
confidence: 99%
“…Clinicopathological characteristics of patients with single hormone receptor-positive breast tumors in the NanoString cohort; differences estimated with t-test (age, Ki67, tumor size) or Fisher's Exact test (grade, estrogen receptor (ER) status, progesterone receptor (PgR) status, human epidermal growth factor receptor 2 (HER2) status, T, N, M); significant results (p-value < 0.05) are in bold. For each analyzed sample, correction and normalization were performed using nSolver 4.0 software, as previously described [14]. In brief, the background level was estimated by thresholding over the mean plus 2 standard deviations of the negative control counts.…”
Section: Nanostring Ncounter Assay For Mirna Profilingmentioning
confidence: 99%
“…This functional duality has been documented for other cancer-associated genes [55,56]. Interestingly, in one recently published study [57], analysis of tumor mRNA expression in a specific cohort of breast cancer patients from the TCGA database showed that high expression of CYLD was linked to shorter disease-free survival. The apparent contradiction between the study by Popeda et al [57] and the study by Hayashi et al [35] may be due to the fact that the former is based on mRNA expression data whereas the Hayashi study was based on protein expression data.…”
Section: Discussionmentioning
confidence: 66%
“…Interestingly, in one recently published study [57], analysis of tumor mRNA expression in a specific cohort of breast cancer patients from the TCGA database showed that high expression of CYLD was linked to shorter disease-free survival. The apparent contradiction between the study by Popeda et al [57] and the study by Hayashi et al [35] may be due to the fact that the former is based on mRNA expression data whereas the Hayashi study was based on protein expression data. Furthermore, it is possible that the role of CYLD in breast cancer development and evolution may depend on the particular type of breast cancer, as well as additional genetic and epigenetic alterations that exist in these tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor derived VEGFC (Vascular endothelial growth factor C) has been demonstrated to support metastatic expansion of primary tumors into the lymphatic vasculature in many tumor types, challenging the traditional concept of a purely passive role of the lymphatic vessels in cancer metastasis [34][35][36]. PSMD7 (26S proteasome non-ATPase regulatory subunit 7) has been reported as overexpressed in a variety of tumors and is hypothesized to be involved in maintenance of proteasome function in cancer cells through its roles in mediating endosomal trafficking and protein recycling [37,38]. This is especially intriguing in the context of our previous discovery of another member of the ubiquitin-proteasome pathway [39], HUWE1, as a plasma EV-associated marker of lung adenocarcinoma with good performance for distinguishing cases from controls [22].…”
Section: Discussionmentioning
confidence: 99%